Pengelolaan Zakat dalam Meningkatkan Kesejahteraan Sosial di wilayah Tertinggal: Analisis Program Kampung Zakat di Besole Tulungagung - Bariroh, Muflihatul (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
The optimization of the Zakat Village program in Besole, Tulungagung, becomes a crucial solution in improving education and social welfare for the local community. This study examines the implementation of the Zakat Village program in Besole, Tulungagung, including the challenges faced, as well as the supporting and inhibiting factors for the success of the program. As a social instrument, zakat holds significant potential in community empowerment, particularly in underdeveloped areas. The programs carried out include the provision of scholarships, tutoring, and capital assistance for local-based businesses, which have proven to improve access to education and increase the income of the community. The success of this program heavily depends on solid collaboration between the managers, government, and the community, as well as active participation from all related parties. However, several challenges such as a lack of understanding of productive zakat, reporting responsibilities, and limited funding remain obstacles that need to be addressed. With a participatory approach, it is hoped that the Zakat Village can continue to advance with innovative programs and have a more significant positive impact. It is expected that this study can contribute substantially to the management of zakat as an effective social empowerment tool and enrich the literature on zakat management. The results of this study can serve as a reference for zakat managers in designing more innovative and sustainable programs to improve the welfare of communities in Tulungagung and other regions.